ANALYSIS OF THE EFFECT OF FINANCIAL PERFORMANCE AND SERVICE PERFORMANCE ON FINANCIAL INDEPENDENCE OF CENTRAL GENERAL HOSPITAL WITH FIXED ASSETS TURNOVER AS A MODERATING VARIABLE IN BLU MINISTRY OF HEALTH - Deby Ayu Octarinda; Idhar Yahya; Muammar Khaddafi (RADJA PUBLIKA, 2025)
This study aims to determine and analyze the effect of financial performance and service performance on the financial independence of the central general hospital at the BLU of the Ministry of Health. The population in this study were all vertical BLU General Hospitals of the Ministry of Health of the Republic of Indonesia registered with the Directorate General of PPK BLU of the Ministry of Finance as many as 13 hospitals during the 2016-2019 period. Sampling of this research was carried out using the purpose sampling method, namely the technique of determining the sample with special considerations so that it was worthy of being a sample. The analytical method used is descriptive statistical test, classical assumption test, multiple linear regression analysis with statistical data processing software tools, namely Eviews. The results of this study indicate that inventory turnover, BOR and TOI have a positive effect on hospital financial independence. Meanwhile, cash ratio, current ratio, receivable collection period, AVLOS and BTO have no effect on hospital financial independence.